Design of a Phospor Photo Stimulation Dosimeter with Webcamera Reader as an Individual Monitor of Occupational Radiation Exposure - Masrochah, Siti; Nur, Muhammad; Suwondo, Ari; Agusyahbana, Farid (South Eastern European Journal of Public Health, 2024)
Introduction: Besides having benefits for diagnostic imaging, radiation also has side effects in the form of biological effects that can endanger radiation workers. In accordance with the provisions of the Nuclear Energy Regulations (Bapeten) No. 4 of 2020, all radiation workers must be monitored for radiation obtained through personal dosimeters. Objectives: Radiological installations process images with radiography computers, which can respond to radiation exposure when processed with radiography computers in the form of exposure index (EI), so it is necessary to develop using photostimulation phosphor (PSP) material, which can be read with Computer Radiography (CR) which is generally already owned by radiological installations. Methods: This research is a research and development study conducted by experiments starting with testing the response of PSP materials to exposure parameters including voltage, current, time and irradiation distance to the PSP dosimeter. Results: The results showed a positive response from various exposure parameters, namely there is a relationship between tube voltage and the response of the Phtostimulation detector plate. Conclusions: The PSP dosimeter can respond to changes in voltage, distance, time in detecting radiation in the form of an exposure index which indicates that the PSP dosimeter can monitor the radiation received by Radiation workers (Radiographers).